Monolithically Integrated Polysilicon/Oxide-Semiconductor Hybrid Thin-Film Transistors for Advanced Sensing - Ping-Che Liu; Chun-Jung Su; Pei-Wen Li; Horng-Chih Lin (IEEE Journal of the Electron Devices Society, 2023)
This work reports an ingenious hybrid thin-film transistor (TFT) process platform that allows monolithic integration of poly-Si and oxide-semiconductor (OS) TFT-based circuits using three-mask processes. The effectiveness of the proposed fabrication approach is demonstrated by a hybrid poly-Si/indium-gallium-zinc oxide (IGZO) TFT cell, in which source/drain (S/D) contacts of poly-Si TFTs were simultaneously formed during the fabrication of IGZO TFTs. A thin Ti layer is intentionally inserted between poly-Si and IGZO channels in order to improve the contact resistivity of the $n^{+}$ poly-Si/IGZO structure. The integrated poly-Si/IGZO TFT cells exhibit sharp transition slopes (~ −35 mV/dec) in the transfer curves. With this feature, the sensitivity of the proposed hybrid TFT cells is greatly improved in comparison to individual IGZO TFTs, as evidenced in the detection measurements of NO2 gas.